Medallion „Librarians in time and space”. Samuel von Brukenthal (Confluenţe Bibliologice, 2025)
The article presents Samuel von Brukenthal's activity as a librarian, highlighting his significant contributions to the development of the library and to the promotion of culture and education in Transylvania.
Keywords: Brukenthal Samuel Von (1721 –1803); Romanian personalities